Health Risks of Rainwater Consumption: A Study of Microbiological and Heavy Metal Exposure in Island Areas - Sakati, Sandy Novryanto; Herawati, Herawati; Kanan, Maria; Balebu, Dwi Wahyu (Media Publikasi Cendekia Indonesia, 2025)
Rainwater is a vital water source in island regions, including North Bulagi District, Banggai Kepulauan Regency, Indonesia. This study aimed to evaluate the quality of harvested rainwater and assess associated health risks from microbiological and chemical contaminants. A cross-sectional design was employed, involving the collection of eight rainwater samples from household reservoirs using purposive sampling and data from 94 respondents to support an exposure assessment. The parameters analyzed included Total Coliform, Escherichia coli, Nitrate (NO₃⁻), Cadmium (Cd), Lead (Pb), and Fluoride (F). Water quality analysis was conducted following APHA standard procedures. Health risk assessments were conducted using the Environmental Health Risk Assessment (EHRA) framework for chemical exposure and Quantitative Microbial Risk Assessment (QMRA) for microbial hazards. Results showed that microbiological contamination, particularly Total Coliform, exceeded the acceptable limit at all sampling points, with the highest level recorded at Point VIII (2,600 CFU/100 mL). Most chemical parameters were within permissible levels; however, Nitrate concentrations at several locations approached the WHO guideline limit, notably at Point II (11.8 mg/L). Health risk assessment indicated a higher potential for non-carcinogenic effects among children due to Fluoride exposure (HQ > 1). Carcinogenic risks from Cadmium and Lead were within acceptable tolerable limits (ILCR < 1.0E-04). These findings underscore the importance of regularly monitoring rainwater quality and implementing mitigation strategies such as first-flush systems, filtration, and disinfection. The integrated methodological approach adopted in this study provides a robust evidence base for the formulation of effective environmental health interventions and policies, particularly in remote and island communities.